THE ISLAMIC SOCIAL IDEOLOGY IN WILLIAM WORDSWORTH’S POEM - Hartono, Rodi (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2016)
The socialism is the basic ideology for many ideologies in the world. Even Indonesian ideology also adapted the socialist ideology (Pancasila doctrines). In this study the researcher would like to search and know about the development of social idealism in Islam. And how the people apply the ideology in the daily activities.The aim of this research of this study is to identify the extent of Islamic socialism influence in Wordsworth’s poem. This is a content analysis research. The researcher analyzed the content of the poems. And the type of the content analysis anylisis applied in the study is the propoganda analysis.The results of the research showed that the researcher just discovered 163 data talked about the socialism in the poem of William Wordsworth in this research, the researcher explained about Lower Social Class People and Hope of Socialism (Freedom and Equality or brotherhood).